The Role of Mediators in Dispute Resolution Based on Progressive Law to Achieve Substantive Justice - Sutarjo Sutarjo; Diah Pudjiastuti (TRUNOJOYO LAW REVIEW, 2026)
This study aims to analyze the role of mediators in criminal dispute resolution within the framework of progressive legal theory to achieve substantive justice. It addresses the inconsistency between the ultimum remedium principle, which positions criminal punishment as a last resort, and the restrictive regulatory framework governing penal mediation in Indonesia. The study contributes a conceptual and critical evaluation of how restorative justice regulations limit mediators' authority and hinder the broader institutionalization of penal mediation within the criminal justice system. It proposes harmonizing restorative justice policies with progressive law to strengthen mediation as a humane and participatory mechanism. This research employs doctrinal legal research using statutory and conceptual approaches. The data were analyzed qualitatively through systematic and conceptual interpretation. The findings indicate that although restorative justice has been formally recognized, strict limitations on offense types, loss thresholds, non-recidivism, and victim consent significantly restrict penal mediation. Consequently, criminal case resolution remains predominantly formalistic and litigation-oriented. The study concludes that regulatory rigidity obstructs the realization of substantive justice. It recommends comprehensive legal reform to expand mediators’ authority and integrate penal mediation more fully into Indonesia’s criminal justice system in line with progressive legal principles.